G5: Coordination and Change Enabling - Collis, William (2011)
Project G5 is the “Coordination and Change-Enabling” project for the Ganges Basin Development Challenge. The Project G5 objective is “To enhance impacts in Bangladesh and India through stakeholder participation, policy dialogue and effective coordination among other Government, NGO’s, CGIAR and donors sponsored projects and programs in the Ganges BDC research Program” There are two major, inter-related activities: (i) coordination with our partners in Project G1-G4; and (ii) enabling change. Project G5 is responsible for maintaining the coherence, integration and focus with our partners leading Projects G1 to G4, through active leadership and ensuring effective communication among projects. Building upon the Ganges BDC impact pathways, Project G5 will lead and coordinate monitoring and evaluation of project progress and integration, with close attention to the quality of implementation, and research products emerging from individual projects. Project G5 will utilize tools of Results Based Management (RBM) to ensure that Projects 1-4 are well integrated into a program of research that ultimately delivers change – development outcomes and impacts. RBM is an approach to adaptive management that strongly emphasizes participation and learning. Learning depends on good information and feedback that will be derived from and delivered by an effective M&E system. G5 connects the research under each project across topics and scales, from household agriculture-aquaculture farming systems to community polder water management through to broader land use planning. The project is also an interface between the program and a variety of existing and potential stakeholders and works towards scaling out of research results to multiple stakeholders with common interest in achieving the BDC. Project G5 outputs are knowledge sharing products such as: (i) policy briefs and other interventions tailored for policy makers; (ii) capacity building tools; (iii) demonstrated approaches for scaling out; (iv) scenarios for climate and hydrological change; and (v) outputs from innovation research. These will be achieved in various ways through activities involving coordination, identifying and enabling partnerships for change; innovation research; development and implementation of a communications strategy; operation of an adaptive management system; support to capacity building; and more generally serving in a leadership and team building role for the Ganges BDC. Impacts will include reduced poverty, improved food security and strengthened livelihood resilience for people in coastal Bangladesh and India.